Serum biomarkers at disease onset for personalized therapy in multiple sclerosis - Monreal, Enric; Fernández-Velasco, José Ignacio; Álvarez-Lafuente, Roberto; Sainz de la Maza, Susana; García-Sánchez, María Isabel; Llufriu, Sara; Casanova, Bonaventura; Comabella, Manuel; Martínez-Yélamos, Sergio; Galimberti, Daniela; Ramió-Torrentà, Lluís; Martínez-Ginés, María Luisa; et al. (Brain (London, England : 1878), 2024)
Abstract The potential for combining serum neurofilament light chain (sNfL) and glial fibrillary acidic protein (sGFAP) levels to predict worsening disability in multiple sclerosis remains underexplored. We aimed to investigate whether sNfL and sGFAP values identify distinct subgroups of patients according to the risk of disability worsening and their response to disease-modifying treatments (DMTs). This multicentre study, conducted across 13 European hospitals, spanned from 15 July 1994 to 18 August 2022, with follow-up until 26 September 2023. We enrolled patients with multiple sclerosis who had serum samples collected within 12 months from disease onset and before initiating DMTs. Multivariable regression models were used to estimate the risk of relapse-associated worsening (RAW), progression independent of relapse activity (PIRA) and Expanded Disability Status Scale (EDSS) score of 3. Of the 725 patients included, the median age was 34.2 (interquartile range, 27.6–42.4) years, and 509 patients (70.2%) were female. The median follow-up duration was 6.43 (interquartile range, 4.65–9.81) years. Higher sNfL values were associated with an elevated risk of RAW [hazard ratio (HR) of 1.45; 95% confidence interval (CI) 1.19–1.76; P < 0.001], PIRA (HR of 1.43; 95% CI 1.13–1.81; P = 0.003) and reaching an EDSS of 3 (HR of 1.55; 95% CI 1.29–1.85; P < 0.001). Moreover, higher sGFAP levels were linked to a higher risk of achieving an EDSS score of 3 (HR of 1.36; 95% CI 1.06–1.74; P = 0.02) and, in patients with low sNfL values, to PIRA (HR of 1.86; 95% CI 1.01–3.45; P = 0.04). We also examined the combined effect of sNfL and sGFAP levels. Patients with low sNfL and sGFAP values exhibited a low risk of all outcomes and served as a reference. Untreated patients with high sNfL levels showed a higher risk of RAW, PIRA and reaching an EDSS of 3. Injectable or oral DMTs reduced the risk of RAW in these patients but failed to mitigate the risk of PIRA and reaching an EDSS of 3. Conversely, high-efficacy DMTs counteracted the heightened risk of these outcomes, except for the risk of PIRA in patients with high sNfL and sGFAP levels. Patients with low sNfL and high sGFAP values showed an increased risk of PIRA and achieving an EDSS of 3, which remained unchanged with either high-efficacy or other DMTs. In conclusion, evaluating sNfL and sGFAP levels at disease onset in multiple sclerosis might identify distinct phenotypes associated with diverse immunological pathways of disability acquisition and therapeutic response. Monreal et al. show that assessing serum neurofilament light chain and glial fibrillary acidic protein levels within a year of multiple sclerosis onset can help identify the risk of disability worsening and the likelihood of a treatment response. These markers could aid the transition to a more personalised therapeutic approach.